Synthesis, characterization, biological activity and equilibrium studies of cadmium(II) with 2,6-diaminopyridine and various bio-relevant ligands - Shoukry, Azza Abdelwahab; Al-Mhayawi, Saedah Rwede (European Journal of Chemistry, 2013)
The complexing properties of 2,6-diaminopyridine (DAP) with cadmium(II) were investigated via measuring pH (i.e., pH-metrically). Binary and ternary complexes of Cd(II) involving DAP and various biologically relevant ligands are investigated. The ligands used (L) were amino acids, dicarboxylic acids, amides and DNA unit constituents. The ternary complexes are formed by simultaneous reactions. The results showed the formation of Cd(DAP)(L) complexes with amino acids and dicarboxylic acids. Amides form both Cd(DAP)(L) complex and the corresponding deprotonated amide species Cd(DAP)(LH-1). The concentration distributions of the various complex species formed in solution were also evaluated as a function of pH. The effect of dioxane as a solvent on the protonation constant of DAP and the formation constants of Cd(II)-DAP complexes were discussed. The solid complexes [Cd(DAP)L)] where L = methionine and glycine, were isolated and characterized. The isolated solid complexes have also been screened for their antimicrobial activities against some selected bacteria and fungi. The activity data show that the complexes are found to have antibacterial and antifungal activity.